Recruitment of family caregivers of persons with dementia: Lessons learned from a pilot randomized controlled trial - Joshi, Sama; Park, Taeyoung; Brody, Lilla; Cruz, Kiana; Mukhi, Priya; Reid, M. Carrington; Herr, Keela; Pillemer, Karl; Riffin, Catherine (Frontiers in Pain Research, 2023)
Family caregivers play an essential role in supporting the health and well-being of older adults with dementia, a population projected to increase rapidly over the coming decades. Enrolling caregivers of people with dementia (PWD) in research studies is vital to generating the evidence necessary to support broader implementation of efficacious intervention programs in real-world care delivery, but a range of challenges impede recruitment and enrollment of sufficiently large and representative sample sizes. In this article, we characterize the challenges and lessons learned from recruiting caregivers of PWD to participate in a pilot randomized control trial. We utilize Bronfenbrenner's ecological model to categorize the challenges into three levels: individual (i.e., understanding caregivers’ time constraints and motivations), community (i.e., reaching underrepresented populations and accessing caregiver support groups) and institutional (i.e., obtaining informed consent and navigating research registries). We found that establishing rapport and maintaining flexibility with participants was crucial for motivating individuals to enroll in our study. Building trust with local communities by collaborating with support group leaders, appointing a co-investigator who is already embedded within a given community, and establishing equitable partnerships with organizations increased recruitment rates. At the institutional level, engaging experts in regulatory affairs and geriatrics may help overcome barriers in obtaining approval from institutional review boards. We also recommend using research registries of individuals who offer their contact information to researchers. The lessons learned from our research—including the challenges and potential solutions to overcome them—may promote more effective and efficient recruitment in future research.